GRANITE-FLUID INTERACTION AT NEAR-EQUILIBRIUM CONDITIONS: EXPERIMENTAL AND THEORETICAL CONSTRAINTS FROM SR CONTENTS AND ISOTOPIC RATIOS - Zuddas P.; Seimbille F.; Michard G. (My University, 1995)
Fluid-granite interaction at near-equilibrium conditions was investigated by doping an experimental system with 84Sr. Reactions were performed at 453 K, saturated vapour pressure, and fluidrock ratio of 20. The initial composition of the experimental fluid corresponded to the theoretical saturation with respect to kaolinite, quartz, laumontite, low-temperature albite, calcite and adularia. Sr was used to trace parent-mineral dissolution, neogenic phase precipitation, and to identify the reactions at Sr2+ steady state.The interaction is described, initially, by the isotopic mixing of the solution (84Sr86Sr)solution ratio and the granite (87Sr86Sr)rock ratio. However, in the rock end-member every main mineral has a different 87Sr86Sr ratio. The evolution of87Sr86Sr ratio in solution as a function of 84Sr86Sr showed that in the early stage of the interaction (where the dissolution of the rock is the dominant reaction) 87Sr-enriched phases, such as biotite, strongly influence the isotopic budget. After some time, the87Sr86Sr ratio of the fluid approaches the Sr isotopic ratio of the bulk rock, suggesting that fluid-granite isotopic equilibration is attained. When the dissolution of the granite is stopped and once the Sr2+ concentration reached steady state, variations of the84Sr86Sr ratio with time can be interpreted by an isochemical dissolution-precipitation of neogenic phases.